2006
DOI: 10.1063/1.2203966
|View full text |Cite
|
Sign up to set email alerts
|

Blue luminescent isolated Alq3 molecules in a solid-state matrix

Abstract: Thin vacuum deposited films of aluminum tris(8-hydroxyquinolinate) (Alq3) embedded in SiO2 matrix at concentrations corresponding to a single-molecule distribution are investigated. The spectral properties of the films are studied by luminescence spectroscopy. It is established that the dilution of Alq3 in the matrix leads to blueshift of the luminescence maximum up to 0.28eV compared to pure Alq3 layers. In contrast to the recently reported facial isomer of Alq3 in the crystalline δ phase, we conclude from ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 10 publications
1
25
0
Order By: Relevance
“…However, the existence of the fac isomer was not excluded as a minority form. In the case of SiO 2 matrix [11] only PL spectroscopy was performed, and it was found that the decreasing of concentration of Alq 3 is accompanied by a blueshift in the emission, even more consistent than the one found in Ar matrix. From the blueshift and effects due to the matrix evaporation rate, it was concluded that the mixed film of Alq 3 and SiO 2 contains both fac and mer isomers in consistent amounts.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…However, the existence of the fac isomer was not excluded as a minority form. In the case of SiO 2 matrix [11] only PL spectroscopy was performed, and it was found that the decreasing of concentration of Alq 3 is accompanied by a blueshift in the emission, even more consistent than the one found in Ar matrix. From the blueshift and effects due to the matrix evaporation rate, it was concluded that the mixed film of Alq 3 and SiO 2 contains both fac and mer isomers in consistent amounts.…”
Section: Introductionmentioning
confidence: 65%
“…Further studies along this line of research have been performed by using the matrix-isolation method, which consists in trapping the molecules under scrutiny inside a solid matrix, where they can be observed by means of various spectroscopic techniques at very little interaction with their environment. In particular, cold Ar [10] and room temperature SiO 2 [11] matrices have been used to measure carefully infrared and photoluminescence (PL) spectra of so trapped Alq 3 molecules.…”
Section: Introductionmentioning
confidence: 99%
“…A first 5.5 pair dielectric mirror consisting of alternating layers of TiO 2 and SiO 2 is deposited on a glass substrate by electron beam evaporation under high vacuum conditions (8 × 10 −6 mbar with a partial pressure of 2 × 10 −4 mbar of O 2 ). This distributed Bragg reflector (DBR) is designed for a wavelength of 535 nm, matching the emission maximum of the applied organic dye Alq 3 (Levichkova et al 2006). Following the first evaporation process, we attach a mask to the sample surface, using a variety of shapes from round to quadratic and hole diameters between 1 and 8 µm.…”
Section: Samples and Experimentsmentioning
confidence: 99%
“…Flexibility, large area emitting and high efficiency are the most important keys for developing interests to make such systems [4][5][6]. Attempts have been recently done on the synthesis and use of a variety of novel electroluminescent (EL) materials for the construction of reliable OLEDs which can be highly suitable in different aspects like quantum efficiency, charge carrier mobility, thermal stability and processability [7][8][9].…”
Section: Introductionmentioning
confidence: 99%